Legal Solutions for Domestic Violence in Unregistered Marriages in Indonesia: Integrating Maqāṣid al-sharī’ah - Akmal, Andi Muhammad; Mundzir, Chaerul; Asti, Mulham Jaki; Abbas, Rahmawati; Mustafa, Zulhas'ari (El-Usrah: Jurnal Hukum Keluarga, 2024)
This research investigates the legal protection available for domestic violence (KDRT) victims within unregistered marriages (nikah siri) in Indonesia. It assesses the difficulties arising from the lack of formal recognition for these marriages and evaluates how Maqāṣid al-sharī’ah  principles can improve legal protection and fill existing gaps in Indonesian law. The study proposes integrating Indonesian marriage law principles with national frameworks to enhance victim protection. A qualitative approach is used, including descriptive analysis of legal documents, case studies, and jurisprudential interpretations. Data were gathered through literature reviews, document analysis, and interviews with legal experts. The focus is on how Maqāṣid al-sharī’ah  principles apply to Indonesian domestic violence laws and the role of itsbat nikah in providing legal remedies. Findings indicate that Indonesia's current legal system inadequately supports victims of unregistered marriages, creating significant barriers to justice and protection. The research underscores that Maqāṣid al-sharī’ah ’s focus on safeguarding life and lineage can form a solid basis for legal reforms. Itsbat nikah is identified as a key solution for officially recognizing these marriages and enhancing legal safeguards. This research is distinctive in merging Maqāṣid al-sharī’ah  with Indonesian law, presenting a fresh perspective on improving legal protection for victims in unregistered marriages. By aligning Islamic principles with modern legal practices, the study offers a framework to better support and protect victims. The study's implications suggest that integrating Maqāṣid al-sharī’ah  into legal reforms could strengthen protections and foster a more inclusive legal system.